Membangun Kinerja Pegawai Melalui Efektivitas Audit Internal di Perbankan Syariah Maluku Utara - Irfan Zamzam; Sitti Mukarramah (Politeknik Ganesha Medan, 2025)
This study aims to analyze the influence of internal audit effectiveness on employee performance in Islamic banking in North Maluku. Internal audit plays a crucial role in ensuring that company operations adhere to applicable standards and regulations, as well as in detecting and preventing potential errors and fraud. Employee performance in the Islamic banking sector is the primary focus, as optimal performance is key to achieving organizational goals and sustainability. This research employs a quantitative method with data collection techniques through questionnaires distributed to employees of several Islamic banks in the North Maluku region. Data analysis is conducted using linear regression to measure the extent to which internal audit effectiveness impacts employee performance. The results indicate a significant positive relationship between internal audit effectiveness and employee performance, suggesting that effective internal audits can enhance employee performance in Islamic banking. These findings provide important implications for Islamic bank management to strengthen the internal audit function as an effort to improve performance and operational effectiveness.